Some properties for a class of multistage interconnection networks - Hui, S. K.; Seman, K.; Yunus, J. (2000)
Derivations of some properties for multistage interconnection(MIN) will be presented in this paper. These derivations are focused on baseline network, data manipulator(modified version), flip network, indirect binary n-cube network, omega network, and regular SW banyan network with spread and fanout of 2(S=F=2). The derivations contain two parts; part I is a supplementary proof of equations (I) and (2) in [8], part 2 is a proof of connectivity between stages for various MIN as mentioned above. We may use the proof of part 2 to build fault-tolerant feature in various MIN networks.